Taḥlīl al-Akhtā’ al-Naḥwiyyah fī Uţrūḥāt al-Țullabah li Qism Ta’līm al-Lugah al-‘Arabiyyah bi Jāmi’ah al-Islāmiyyah al-Ĥukūmiyyah bi Quds - Syafiq, Nuriya Maulida Khusna; Muflihah, Muflihah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to describe and explore the form of syntactic errors in the theses of PBA IAIN Kudus students in the first and current batches, in the form of syntactic error analysis, which is then evaluated and corrected. The subjects of this research are the theses of PBA IAIN Kudus students in the first batch and the current batch. The object of this research is sentences that contain elements of syntactic errors. The method used is a qualitative content analysis approach to errors in the theses of PBA IAIN Kudus students in the first and current batches, using 3 samples in each batch. To find and classify sentences that contain elements of syntactic errors, reading and recording techniques are used. The instrument used is the researcher herself. This study results in 6 syntax errors in the theses of PBA IAIN Kudus students in the first batch (2008) and 26 errors in the current batch (2019). The solutions offered are innovative teaching staff in Arabic language learning, seriousness and concentration in writing theses and taking Arabic language learning seriously.